Thulium oxide nanoparticles as radioenhancers for the treatment of metastatic cutaneous squamous cell carcinoma. (4th November 2020) - Perry, Jay; Minaei, Elahe; Engels, Elette; Ashford, Bruce G; McAlary, Luke; Clark, Jonathan R; Gupta, Ruta; Tehei, Moeava; Corde, Stephanie; Carolan, Martin; Ranson, Marie
Abstract: Metastases from cutaneous squamous cell carcinoma (cSCC) occur in 2%–5% of cases. Surgery is the standard treatment, often combined with adjuvant radiotherapy. Concurrent carboplatin treatment with post-operative radiotherapy may be prescribed, although it has not shown benefit in recent clinical trials in high-risk cSCC patients. The novel high-Z nanoparticle thulium (III) oxide has been shown to enhance radiation dose delivery to brain tumors by specific uptake of these nanoparticles into the cancerous tissue. As the dose-enhancement capacity of thulium oxide nanoparticles following radiotherapy against metastatic cSCC cells is unknown, its efficacy as a radiosensitizer was evaluated, with and without carboplatin. Novel and validated human patient-derived cell lines of metastatic cSCC were used. The sensitivity of the cells to radiation was investigated using short-term proliferation assays as well as clonogenic survival as the radiobiological endpoint. Briefly, cells were irradiated with 125 kVp orthovoltage x-rays (0–6 Gy) with and without thulium oxide nanoparticles (99.9% trace metals basis; 50 µ g ml −1 ) or low dose carboplatin pre-sensitization. Cellular uptake of the nanoparticles was first confirmed by microscopy and found to have no impact on short-term cell survival for the cSCC cells, highlighting the biocompatibility of thulium oxide nanoparticles. Clonogenic cell survival assays confirmed radio-sensitization when exposed to thulium nanoparticles, with the cell sensitivity increasing by a factor of 1.24 (calculated at the 10% survival fraction) for the irradiated cSCC cells. The combination of carboplatin with thulium oxide nanoparticles with irradiation did not result in significant further reductions in survival compared to nanoparticles alone. This is the first study to provide in vitro data demonstrating the independent radiosensitization effect of high-Z nanoparticles against metastatic cSCC with or without carboplatin. Further preclinical investigations with radiotherapy plus high-Z nanoparticles for the management of metastatic cSCC are warranted.